Escola e família: análises dessa relação na educação infantil - Cortese, Caroline Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Considering that the child from the moment he starts attending school remains under the influence of his family, it is of the utmost importance that the relationships established between family and school make possible a climate of trust and mutual respect. In this sense, the general objective of the present study sought to identify the possible relationships between family and school in Early Childhood Education that contribute to the child's learning process. In order to do so, the specific objectives have been directed towards analyzing such relationships, as well as the consequences that the non-participation of the family can cause, both for the development of the child and for the school to carry out its work. And so, analyze ways of contributing the school to expand this relationship. The methodological procedures of this research included: 1) Bibliographic research on the family-school relationship in the legislation; 2) Bibliographical research on the mechanisms of family participation in school; 3) Bibliographical research on the contributions of the family-school relationship to the formation of the child; 4) Collecting, analyzing and presenting the data together with the schools / field through questionnaires with open questions addressed to the two directors, one being a public school and a private school, together with ten parents, five of each school. The data showed, among other aspects, that families and schools consider the relationship between them to be of great importance, so that together they can perform the full development of the child in the best way possible. We believe that the integration between family and school can be considered, if not more important, one of the main points for the improvement of the child's learning in Early Childhood Education, such as socializing, building identity and autonomy, games and games, drawing, painting.

Considerando que a criança a partir do momento em que começa a frequentar o espaço escolar continua sob a influência de sua família, é de suma importância que as relações estabelecidas entre família e escola possibilitem um clima de confiança e respeito mútuo. Nesse sentido, o objetivo geral do presente estudo buscou identificar quais as possíveis relações entre família e escola na Educação Infantil que contribuem com o processo de aprendizagem da criança. Para tanto, os objetivos específicos se encaminharam no sentido de analisar tais relações, bem como as consequências que a não participação da família pode causar, tanto para o desenvolvimento da criança quanto para a escola realizar seu trabalho. E assim, analisar formas de contribuição da escola para ampliar essa relação. Os procedimentos metodológicos desta pesquisa foram: 1) Pesquisa documental sobre a relação escola-família na legislação; 2) Pesquisa bibliográfica sobre os mecanismos de participação da família na escola e as contribuições dessa relação para o desenvolvimento da criança; 4) Coleta, análise e apresentação dos dados juntos às escolas/campo por meio de questionários com questões abertas dirigidas à duas diretoras, sendo uma de escola pública e uma de escola particular, juntamente de dez pais, sendo cinco de cada escola. Os dados demonstraram, entre outros aspectos, que as famílias e as escolas consideram de grande importância a relação entre elas, para que juntas possam realizar da melhor forma o desenvolvimento integral da criança. Acreditamos que a integração entre escola e a família pode ser considerada, senão a mais importante, um dos principais aspectos para a melhoria da aprendizagem da criança na Educação Infantil, como o socializar, construção da identidade e autonomia, jogos e brincadeiras, desenhar, pintar.
Keywords: Educação de crianças; Família; Ensino; Aprendizagem; Learning